2019
DOI: 10.1590/s1980-220x2017023503431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stress in freshman and senior nursing students

Abstract: Objective: To compare stress levels in freshman and senior nursing students. Method: A cross-sectional study was carried out in a public federal university of the state of Bahia, with students who answered questionnaires about sociodemographic variables, academic life, and a scale for assessing stress in nursing students. Chi-square and Fisher’s exact tests were applied to analyze the relationship between variables. To assess proportional trends between ordinal variables and groups, a chi-square test for line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 14 publications
0
18
0
17
Order By: Relevance
“…A recent study showed that second year nursing students report the highest levels of stress, compared to other years, due to their perception of having inadequate knowledge and skills in their clinical rotations (Admi et al, 2018). However, other studies show that the final year of nursing education is the most stressful year (Edwards et al, 2010;He et al, 2018;Jimenez et al, 2010;Mussi et al, 2019). The high levels of stress experienced by final-year students were attributed to demanding clinical settings that require students to master more challenging technical skills and have more in-depth knowledge about patients' medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that second year nursing students report the highest levels of stress, compared to other years, due to their perception of having inadequate knowledge and skills in their clinical rotations (Admi et al, 2018). However, other studies show that the final year of nursing education is the most stressful year (Edwards et al, 2010;He et al, 2018;Jimenez et al, 2010;Mussi et al, 2019). The high levels of stress experienced by final-year students were attributed to demanding clinical settings that require students to master more challenging technical skills and have more in-depth knowledge about patients' medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Esse achado vai ao encontro de estudos anteriores que evidenciaram a predominância de estudantes de enfermagem com até 25 anos. (8)(9)(10)(11) Com o objetivo de gerar perspectivas de crescimento e progresso, a entrada de jovens no ensino superior pode ser considerada como um fator positivo, refletindo uma melhora no acesso à formação universitária. Em contrapartida, a opção precoce pela profissão demanda do estudante amadurecimento no que se refere à certeza da escolha pela carreira.…”
Section: Discussionunclassified
“…Os meios de transportes para chegar até a faculdade e os campos de estágios, de um modo geral, são considerados um fator estressante para os acadêmicos (11). A distância percorrida entre a faculdade, os campos de práticas e a residência do acadêmico estimulam altos níveis de estresse devido ao tempo despendido no deslocamento (20).…”
Section: Situações Desencadeadoras De Estresseunclassified
“…Conforme o acadêmico progride no curso de Enfermagem, mais responsabilidades e habilidades lhe são exigidas; nesse contexto, o momento das atividades do estágio é estressante. A relação entre o acadêmico e a equipe de saúde, em ambiente de prática assistencial, provoca alto nível de estresse, já que a maior parte dos acadêmicos é jovem e com pouca experiência de trabalhar coletivamente, além de apresentar habilidades interpessoais ainda em desenvolvimento (20).…”
Section: Situações Desencadeadoras De Estresseunclassified